Immune checkpoint inhibition in small cell lung cancer: a key to reach an unmet need? - Gelsomino, Francesco; Leonetti, Alessandro; Rihawi, Karim; Sperandi, Francesca; Casolari, Laura; Melotti, Barbara; Fiorentino, Michelangelo; Ardizzoni, Andrea (Translational Cancer Research, 2017)
Small cell lung cancer (SCLC), accounting for 13–15% of all lung cancers, is strongly correlated with smoking and it is associated with a poor overall survival (OS) (2-year OS rate: 5%), particularly in patients with extensive disease (1,2).